2020
DOI: 10.1002/ecy.3099
|View full text |Cite
|
Sign up to set email alerts
|

A nucleation framework for transition between alternate states: short‐circuiting barriers to ecosystem recovery

Abstract: The theory of alternate stable states provides an explanation for rapid ecosystem degradation, yielding important implications for ecosystem conservation and restoration. However, utilizing this theory to initiate transitions from degraded to desired ecosystem states remains a significant challenge. Applications of the alternative stable states framework may currently be impeded by a mismatch between local‐scale driving processes and landscape‐scale emergent system transitions. We show how nucleation theory pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(61 citation statements)
references
References 113 publications
0
61
0
Order By: Relevance
“…As such, the regional resiliency noted by Loughlin et al (Loughlin et al, 2018) may be subject to novel vulnerabilities that were not so urgent historically. Michaels et al (2020) have suggested that reforestation efforts should first attempt to diagnose the ecological conditions and feedbacks that allow a basin of attraction for a desired stable state to persist, and also find the minimum “nucleus” area needed for those processes to proceed and grow. They and others, such as some proponents of rewilding (Fernández et al, 2017), suggest seeding landscapes with species consortiums intended to recreate ecological complexity as much as possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, the regional resiliency noted by Loughlin et al (Loughlin et al, 2018) may be subject to novel vulnerabilities that were not so urgent historically. Michaels et al (2020) have suggested that reforestation efforts should first attempt to diagnose the ecological conditions and feedbacks that allow a basin of attraction for a desired stable state to persist, and also find the minimum “nucleus” area needed for those processes to proceed and grow. They and others, such as some proponents of rewilding (Fernández et al, 2017), suggest seeding landscapes with species consortiums intended to recreate ecological complexity as much as possible.…”
Section: Discussionmentioning
confidence: 99%
“…However, great opportunity for the future exists in Los Cedros: the forest of Los Cedros need not be seen as a delicate ecological island in a storm, nor is its protection an academic or moral exercise, or a desperate rear-guard conservation strategy. It is instead useful to think in the sense of Michaels (2020), supported by the long-term observations of Loughlin et al (2018), and see the Los Cedros forest as a nucleus of primary cloud forest that has prospered for thousands of years, that has weathered the recent waves of deforestation, and that now stands ready to help reseed the new forests of the northern Andes. Tables Table 1 -…”
Section: Conservation Value Of Los Cedrosmentioning
confidence: 99%
“…Past applications of ecological nucleation have used it as an analogy to describe the growth of recently established patches of the desired state, which can accelerate that state’s spread (Yarranton and Morrison 1974, Corbin and Holl 2012, Hulvey et al 2017, Shaw et al 2020). More recently, autocatalytic nucleation has been more strictly defined in ecology as the process by which a critical patch size of the desired state can lower resistance thresholds and catalyze rapid growth through local positive feedback dynamics (Michaels et al 2020). In this way, nucleation leverages local‐scale interactions to facilitate transitions between alternate stable states at the landscape scale.…”
Section: Can Nucleation Bridge To Desirable Alternative Stable States? Theory and Applications – A Review Of The 2021 Esa Annual Meeting mentioning
confidence: 99%
“…Following Bradley et al (2019), we tested whether the recipient plant community richness was better described by a linear per capita effect of A. leptopus or a non-linear per capita effect. A non-linear per capita effect would suggest density-dependent impacts, which may depend on the invasive species exceeding a critical abundance threshold, for example (Thiele et al 2010;Bradley et al 2019;Michaels et al 2020). Specifically, we fitted both linear and a nonlinear regression models and tested significance of (non-)linear model terms using the confidence intervals of the regression coefficients.…”
Section: Impact On Species Richness and Evenness And Mediation By Land Cover Typementioning
confidence: 99%